2009
DOI: 10.1007/s12011-009-8456-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age and Gender on 37 Chemical Element Contents in Scalp Hair of Healthy Humans

Abstract: The effect of age and gender on minor and trace element contents in the scalp hair of 80 relatively healthy 15- to 55-year-old women and men was investigated. Contents or upper limit of contents of 37 chemical elements in the scalp hair were determined by instrumental neutron activation analysis. Mean values (M +/- SEpsilonMu) for the mass fraction of Ag, Au, Ba, Br, Ca, Ce, Cl, Co, Cr, Eu, Fe, Hf, Hg, I, K, La, Lu, Mg, Mn, Na, Rb, Sb, Sc, Se, Sm, Sr, Th, and Zn (milligrams per kilogram of dry hair) were 0.191… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 17 publications
7
37
0
1
Order By: Relevance
“…113 In other studies, Zn, Na and Pb were higher in boys, while Fe and Bi were higher for girls. 114 Other correlations with age for Ce, La and Th increasing with age were only significant for females and not males. 114 Other correlations with age for Ce, La and Th increasing with age were only significant for females and not males.…”
Section: Gendermentioning
confidence: 91%
“…113 In other studies, Zn, Na and Pb were higher in boys, while Fe and Bi were higher for girls. 114 Other correlations with age for Ce, La and Th increasing with age were only significant for females and not males. 114 Other correlations with age for Ce, La and Th increasing with age were only significant for females and not males.…”
Section: Gendermentioning
confidence: 91%
“…The spectrometer provided a resolution of 1.9 keV on the 60 Co 1332 keV line. Details of used nuclear reactions, radionuclides and gamma-energies were presented in our earlier publications concerning the INAA chemical element contents in human prostate and scalp hair [43,44].A dedicated computer program for INAA mode optimization was used [45]. All thyroid samples were prepared in duplicate and mean values of trace element contents were used in final calculation.…”
mentioning
confidence: 99%
“…They also noted the lower Zn content in hair for chil dren and males over 60 years. An increase in Ce (cerium), La (lanthanum), Th (thorium), and Rb (rubidium) content in hair as well as a drop in Cl (chloride) content, depending on age, was proved by Zaichick and Zaichick [21], Other authors [22] reported decline in the concentration of Li in scalp hair with age. Moreover, these authors pointed out that the level of Li in hair can be very low, even un detectable for all age groups.…”
Section: Correlations Between the Contents Of Elements And Agementioning
confidence: 91%